Effects of human walking on the capture efficiency of range hood in residential kitchen. (June 2021) - Lv, Lipeng; Zeng, Lingjie; Wu, Yuhang; Gao, Jun; Xie, Wuhao; Cao, Changsheng; Chen, Yuqing; Zhang, Jing
Abstract: Flow characteristics induced by human walking and the effect of human walking on the performance of range hood in residential kitchen were investigated by performing transient CFD simulation with dynamic mesh method. Transient capture efficiency was used to evaluate the effect of human walking on range hood. Tracer gas experiment and visualization experiment were conducted. Results showed that the process of human walking could be divided into five stages, and the interaction between wake and thermal plume was the main reason for the fluctuation of the thermal plume. The capture efficiency had a decrement of 0.5 at the most unfavorable conditions. The factor analysis involved intensity of heat source, exhaust rate, walking speed, and distance between human and counter and showed that the parameters related to human walking were significant contributors to the undulation of capture efficiency. Air curtain range hood was introduced in this study to assess its function to resist the effect of human walking. Compared with increasing the exhaust rate, air curtain could prevent the effect induced by human walking with less increment in air volume, which saved energy that would be wasted on increasing the exhaust rate. This study extended the understanding of human walking and its effect and helped in comprehending the similar condition where pollutant/heat source and human activity existed. Highlights: CFD simulation combined dynamic mesh method was applied in investigating the effect of human walking on range hood. The morphology of thermal plume was destroyed due to the mutual effect of wake and thermal plume. Significant sequence of factors: distance between human and counter > walking speed > intensity of heat source> exhaust rate. Air curtain range hood was verified as a feasible method to resist the effect of human walking.